Mycobacterium tuberculosis Responds to Chloride and pH as Synergistic Cues to the Immune Status of its Host Cell - Tan, Shumin; Sukumar, Neelima; Abramovitch, Robert B.; Parish, Tanya; Russell, David G. (PLoS pathogens, 2013)
The ability of Mycobacterium tuberculosis (Mtb) to thrive in its phagosomal niche is critical for its establishment of a chronic infection. This requires that Mtb senses and responds to intraphagosomal signals such as pH. We hypothesized that Mtb would respond to additional intraphagosomal factors that correlate with maturation. Here, we demonstrate that [Cl⁻] and pH correlate inversely with phagosome maturation, and identify Cl⁻ as a novel environmental cue for Mtb. Mtb responds to Cl⁻ and pH synergistically, in part through the activity of the two-component regulator phoPR. Following identification of promoters responsive to Cl⁻ and pH, we generated a reporter Mtb strain that detected immune-mediated changes in the phagosomal environment during infection in a mouse model. Our study establishes Cl⁻ and pH as linked environmental cues for Mtb, and illustrates the utility of reporter bacterial strains for the study of Mtb-host interactions in vivo.